Non Alcoholic Fatty Liver Disease: A Silent Global Epidemic (Bangladesh Journal of Medicine, 2023)
Nonalcoholic fatty liver disease (NAFLD) is a common liver disease worldwide affecting adult as well as children with an increasing prevalence. It is associated with insulin resistance and frequently occurs with features of the metabolic syndrome. NAFLD is a spectrum, with NAFL (Non-alcoholic fatty liver) being the initial mildest form, NASH and cirrhosis is being at the other end of the spectrum. Mostly NAFLD is asymptomatic but may present with elevated liver enzyme levels to cirrhosis with its complications and hepatocellular carcinoma. Standard ultrasound including elastography may be used to detect steatosis. Though, liver biopsy is the gold standard for diagnosis of NAFLD but it is not frequently performed. NAFLD patients with evidence of nonalcoholic steatohepatitis and advanced fibrosis are at increased risk of adverse outcomes, including overall mortality.  Life style modification and weight loss remains the cornerstone of the management of NAFLD. There are no approved pharmacological drugs for the treatment of NAFLD till now. Although several promising drugs are on the horizon, more trials are needed to validate these medications.Bangladesh J Medicine 2023; 34(2): 73-79